Remote monitoring of a premature infants incubator - Ali Ghazi Shabeeb; Ali Jaber Al-Askery; Zainab Majid Nahi (Institute of Advanced Engineering and Science, 2020)
In this paper, the air temperature and humidity levels in the infant' incubator are monitored remotely by means of Arduino microcontroller with different sensors and an open source internet of things (IoT) applications. The system is connected to a network via a wireless fidelity (Wi-Fi) connection to be linked to an application on the smart phone or to the computer. The system is designed using Arduino microcontroller, DHT11/DHT22 sensor for measuring the body parameters, such as the temperature and the humidity, LCD monitor, ESP8266 WiFi modules, and NodeMCU-v3.The results have shown that real time updated medical records can be transferred to the medical staff utilizing ThingSpeak IoT applications.